QUALISIGN, SINSIGN, AND LEGISIGN IN GREAT EXPECTATIONS BY CHARLES DICKENS - Rachma Fira (Univeristas Islam Negeri (UIN) Alauddin Makassar, 2021)
This study aims to describe the semiotics of Charles Sanders Pierce based on the representament in the novel. This research is a qualitative descriptive study. The Great Expectations, novel by Charles Dickens as a source of research data and text excerpts in the form of narration, dialogue, and monologues containing qualisign, sinsign, and legisign as data. Data collection techniques are done by reading techniques and inventory techniques. Stages of data analysis techniques are carried out by means of data reduction, data presentation, explanation of the results of the study as well as the conclusion and verification of research results. The results showed that the semiotics in the novel Great Expectations by Charles Dickens were divided into: (1) qualisign in the form of verbal markers in the form of characters' conversations about other characters and nonverbal markers in the form of activities or activities of characters, time settings, and character reactions. (2) sinsign in the form of verbal markers of the character's conversations with other characters and conversations about other characters as well as nonverbal markers in the form of bodily movements or expressions, character's activities or activities, character's physical characteristics, settings, thoughts or feelings of the characters, and character's reactions. (3) Legisign of verbal markers in the form of characters' conversations with other characters and conversations about other characters and nonverbal markers in the form of body movements or expressions of characters.